Genome-resolved analysis of traditional fermented biofertilizers as scalable solutions for soil restoration - Walia, Abhishek; Selvarajan, Ramganesh; Ogola, Henry Joseph Oduor; Chauhan, Rakesh; Bala, Jyoti; Verma, Shailender Kumar; Kumar, Rameshwar (Frontiers in Microbiology, 2025)
Soil degradation threatens global food security by eroding nutrient reserves and biological resilience. Microbial solutions that regenerate soil fertility through ecological processes offer a sustainable alternative to chemical intensification, yet lack mechanistic validation linking genomic potential to field performance. Fermented microbial consortia, naturally assembled through traditional practices worldwide, represent promising but underexplored technologies for biological soil restoration. Here, we integrate shotgun metagenomics, metagenome-assembled genome (MAG) reconstruction, and two-season field trials to evaluate Jeevamrit, a cattle-derived fermented biofertilizer widely used across South Asia, as a model system for understanding microbial-mediated soil restoration. Metagenomic profiling revealed that Jeevamrit fermentation of cattle dung and urine produces a functionally rich microbial consortium dominated by Firmicutes, Proteobacteria, Actinobacteria, and Bacteroidetes. Thirty high-quality MAGs encoded genes for nitrogen fixation (nifHDK), phosphate solubilization (phoA, pstS), potassium transport (trkA, phoR), siderophore biosynthesis, and phytohormone production (trpA, miaB), alongside enriched CAZymes (GH13, PL1) and biosynthetic clusters (NRPS, PKS, terpenes) supporting nutrient turnover and rhizosphere signaling. Field application in severely degraded Himalayan rice soils substantially improved soil health relative to controls: soil organic carbon increased from 0.53%–0.68% to 0.76%–1.04% (up to 96% increase), microbial biomass carbon rose from ~72 mg C kg−1 to 186–282 mg C kg−1 (159% increase), available phosphorus increased 39.5%, and grain yield improved 74%, while pH and electrical conductivity remained stable. Principal component analysis confirmed that SOC, microbial biomass, and nutrient availability drove treatment differentiation, corroborating genomic predictions. This genome-to-field framework establishes fermented microbial consortia as multifunctional solutions that restore soil fertility through ecological intensification rather than chemical supplementation. By demonstrating that traditional farmer innovations can be genomically validated and mechanistically understood, this work provides a replicable model for scaling nature-based, low-cost soil restoration technologies to address global agricultural sustainability challenges.